2018
DOI: 10.1002/2017jd027524
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of PM2.5 Concentrations by Aerosol‐Meteorology Interactions Over China

Abstract: Aerosol‐meteorology interactions can change surface aerosol concentrations via different mechanisms such as altering radiation budget or cloud microphysics. However, few studies investigated the impacts of different mechanisms on temporal and spatial distribution of PM2.5 concentrations over China. Here we used the fully coupled Weather Research and Forecasting model with online chemistry (WRF‐Chem) to quantify the enhancement of PM2.5 concentrations by aerosol‐meteorology feedback in China in 2014 for differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 60 publications
6
47
1
Order By: Relevance
“…The Morrison microphysics scheme simulates ACI via linking prognostic aerosols to cloud condensation nuclei. We use a prescribed cloud droplet number concentration (CDNC) of 10 cm −3 in the Morrison microphysics scheme to exclude ACI as well as anthropogenic impacts on clouds (Zhao et al 2017, Zhang et al 2018. Although the CDNC value of 10 cm −3 does not represent the BTH condition, sensitivity simulations with CDNC of 200 cm −3 as will be discussed below show minor changes on our results.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Morrison microphysics scheme simulates ACI via linking prognostic aerosols to cloud condensation nuclei. We use a prescribed cloud droplet number concentration (CDNC) of 10 cm −3 in the Morrison microphysics scheme to exclude ACI as well as anthropogenic impacts on clouds (Zhao et al 2017, Zhang et al 2018. Although the CDNC value of 10 cm −3 does not represent the BTH condition, sensitivity simulations with CDNC of 200 cm −3 as will be discussed below show minor changes on our results.…”
Section: Methodsmentioning
confidence: 99%
“…Here we use the coupled meteorology-chemistry model WRF-Chem to address this issue. A recent WRF-Chem modeling study has found that the ACI effects are much smaller than ARI over the BTH region in fall and winter (Zhang et al 2018), when severe haze episodes occur frequently. Besides, ACI effects are highly uncertain in current models (Boucher et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies examining how aerosols interact with weather and climate remain uncertain and limited. Recently, with the rapid development of coupled meteorology and chemistry models, many new studies have been conducted to investigate the aerosol direct and indirect effects and feedbacks (Baklanov et al, 2017;Forkel et al, 2015;Gao et al, 2016Gao et al, , 2017Grell et al, 2005;Han, 2010;Huang et al, 2016;Jacobson et al, 2007;Saide et al, 2012;Yang et al, 2011;Zhang et al, 2010). In highly polluted regions like Asia, aerosol feedbacks can be particularly important (Gao et al, 2016(Gao et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the aerosol‐meteorology interactions can in turn change surface aerosol concentrations. Recent studies reveal that both aerosol‐radiation and aerosol‐cloud interactions increase surface aerosol concentration (Wang, Wang, et al, ; Zhang et al, , ). Nevertheless, the underlying mechanism is rarely discussed in the PRD region and needs to be further investigated.…”
Section: Introductionmentioning
confidence: 99%